Midwives' perceptions of patient safety and their impact on patient outcomes: systematic review - Fajar Rubianti; Budi Aji; Joko Mulyanto (Jurnal Kesehatan Ibu dan Anak, 2026)
Patient safety is a global health priority, particularly in maternity care, where midwives are central to ensuring safe maternal and neonatal outcomes. Yet, their own perceptions of safety remain underexplored. This systematic literature review aimed to synthesise evidence on midwives’ perceptions of patient safety and examine how these perceptions influence maternal and neonatal outcomes. The review followed PRISMA 2020 guidelines and used the JBI Critical Appraisal Checklist for quality assessment. Literature searches were conducted in PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2020 and 2025. Eligible studies included quantitative research exploring midwives’ safety perceptions and related outcomes. From 250 identified records, four studies met the inclusion criteria.. Findings revealed that midwives’ perceptions of safety were shaped by staffing adequacy, work environment, managerial support, and communication systems. Understaffing of registered midwives was associated with an 11% increase in harmful incidents, and high patient turnover with a 19% increase in adverse events. Structured feedback and leadership-driven action planning improved teamwork climate and job satisfaction. Positive work environments correlated with stronger safety culture and intent to remain in the profession. Additionally, communication tools supporting woman-centred care enhanced shared decision-making and improved labour experiences. Midwives’ perceptions of safety reflect real systemic risks and can serve as early indicators of maternal care quality. Strengthening staffing levels, fostering supportive organisational cultures, and promoting woman-centred practices are critical to enhance both patient outcomes and workforce stability.